2016
DOI: 10.1016/j.btre.2016.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cellobiose dehydrogenase and laccase containing culture fluids of Termitomyces sp. OE147 for degradation of Reactive blue 21

Abstract: HighlightsUse of culture filtrates of Termitomyces sp. OE147.Decolourization and degradation of Reactive blue 21.Cellobiose dehydrogenase and laccase as effective redox couple.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…These amino-acid compositions vary from one geographic region to another. Laccase enzyme which is known to play a key role in biosynthesis of melanin has been also reported from Termitomyces (Bose et al 2007; Gangwar et al 2016). Rahmad et al (2014) identified sulphite reductase enzyme from T. heimii which plays a key role in sulphur assimilation.…”
Section: Discussionmentioning
confidence: 92%
“…These amino-acid compositions vary from one geographic region to another. Laccase enzyme which is known to play a key role in biosynthesis of melanin has been also reported from Termitomyces (Bose et al 2007; Gangwar et al 2016). Rahmad et al (2014) identified sulphite reductase enzyme from T. heimii which plays a key role in sulphur assimilation.…”
Section: Discussionmentioning
confidence: 92%
“…Screened fungal isolate was subjected to quantitative estimation of lignolytic enzymes following standard protocol i.e., cellulase [28] and xylanase [29]. Fungal isolates were grown in Czapek-dox broth (MgSO4.7H2O -0.5g/L;FeSO4 -0.01g/L;KCl -0.5g/L;KH2PO4 -1g/L ;NaNO3-3g/L;pH -6.0-6.5) with 1% of respective carbon source i.e., carboxy methyl cellulose (CMC) for cellulase and xylan for xylanase.…”
Section: Quantitative Assay Of Ligninolytic Enzymesmentioning
confidence: 99%
“…produces ligninolytic enzymes i.e. cellobiose dehydrogenase, xylanase and other lignocellulosic enzymes exudated by the fungus [29,35,36]. Reason behind dye decoloration might be due to the enzymatic degradation and Congo red degraded products might be adsorbed with the cell wall material of fungus.…”
Section: Termitomycesmentioning
confidence: 99%
“…Laccase (LAC, EC 1.10.3.2), p-diphenol oxidase, needs to be added simultaneously into the system as a regenerative enzyme to oxidise redox mediators that serve as an electron acceptor for CDH [10,11]. This enzyme is included in multicopper oxidases (MCOs) and can oxidise organic and inorganic compounds such as mono-, di, poly, amino-, and methoxyphenols and several aromatic amines [12] with concurrent reduction of molecular oxygen to water.…”
Section: Introductionmentioning
confidence: 99%